Onward with the Cordillera indigenous women's struggle for liberation, democracy, and self-determination - Castro-Palaganas, Erlinda (2010)
Abstract: To the women of the Cordillera region in the Philippines, the present situation is a lingering source of new problems and challenges. The vast natural wealth of the Cordilleras has been the target of state development aggression. This development thrust is anchored to globalization policies such as privatization, deregulation, and liberalization, and the effects have impoverished, not improved, people's lives. The corporate mining and logging operations arising from the government's national mineral liberalization program have not only destroyed the environment but violated indigenous people's rights. To the indigenous peoples ancestral land is not just a home but their survival. The resulting faces of hunger and poverty, militarization, violence, migration, oppression, and displacement, among many other issues, have profoundly affected women's well being. But on the other hand, these situations have also pushed women to join other sectors to defend their rights and continue their struggle for self‐determination. The history of indigenous women?s activism in the Cordillera shows decades of militant work with nongovernment organizations, support groups, and advocates. Innabuyog, an alliance of women's organizations in the Cordillera region, has taken on the struggles of the women of the Cordillera and their enduring resistance and fighting spirit to protect their land, life, and resources. The Cordillera women's collective struggle for liberation, democracy, and self-determination is and will be a continuing challenge for as long as women's rights in the Cordillera are violated.
History of indigenous women's activism in the Cordillera -- The challenges of Cordillera women today : poverty and development -- Gender issues in the face of poverty and underdevelopment -- Globalization versus the well-being of the Cordillera indigenous women -- Political repression and militarization to protect global and capitalist interests -- Indigenous women's activism : it's relevance to the Cordillera women's struggle for liberation , democracy , and self-determination -- Solarity work among and with other women's organizations and support groups -- Women's involvement to advance "new politics for change" -- Restoring Lipan apache woman's laws, lands, and strength in El Calaboz Rancheria at the Texas-Mexico border.
Photocopy.
Includes bibliographical references (p. 558)
Keywords: Indigenous women -- Cordillera Region -- Social conditions; Indigenous women -- Cordillera Region -- Political activity; Feminism -- Philippines -- Cordillera Region; Women -- Philippines -- Cordillera Region -- Social conditions; Women -- Philippines -- Cordillera Region -- Economic conditions